1999
DOI: 10.1074/jbc.274.35.24973
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of Novel Mouse and Human Secretory Phospholipase A2s

Abstract: Mammalian secretory phospholipase A 2 s (sPLA 2 s) are classified into several groups according to molecular structure and the localization of intramolecular disulfide bridges. Among them, group IIA sPLA 2 has been thought to be one of the key enzymes in the pathogenesis of inflammatory diseases owing to its augmented expression under various inflammatory conditions. However, in a number of inbred mouse strains, the group IIA sPLA 2 gene is naturally disrupted by a frameshift mutation. Here, we report the clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
104
0
4

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(113 citation statements)
references
References 60 publications
5
104
0
4
Order By: Relevance
“…The heterogeneous glycosylation pattern of hGIID appears to be similar to those observed for bee venom sPLA 2 or other proteins endogenously or heterogeneously expressed in insect cells (46 -48). Treatment of glycosylated hGIID with N-glycopeptidase (Roche Molecular Biochemicals) followed by mass spectrometry analysis confirmed that hGIID produced in S2 cells is N-glycosylated (not shown), in good agreement with the presence of an N-glycosylation site in its sequence (49). On the other hand, treatment with O-glycosidase and neuraminidase (Roche Molecular Biochemicals) does not affect the molecular mass of the glycosylated hGIID protein, suggesting the absence of sialic acids and Oglycosylation (not shown).…”
Section: Methodsmentioning
confidence: 73%
See 1 more Smart Citation
“…The heterogeneous glycosylation pattern of hGIID appears to be similar to those observed for bee venom sPLA 2 or other proteins endogenously or heterogeneously expressed in insect cells (46 -48). Treatment of glycosylated hGIID with N-glycopeptidase (Roche Molecular Biochemicals) followed by mass spectrometry analysis confirmed that hGIID produced in S2 cells is N-glycosylated (not shown), in good agreement with the presence of an N-glycosylation site in its sequence (49). On the other hand, treatment with O-glycosidase and neuraminidase (Roche Molecular Biochemicals) does not affect the molecular mass of the glycosylated hGIID protein, suggesting the absence of sialic acids and Oglycosylation (not shown).…”
Section: Methodsmentioning
confidence: 73%
“…Although we did not study mouse group XII, this sPLA 2 is also reported to have low phospholipase activity after refolding of inclusion body protein expressed in E. coli (64). Also, the enzymatic activity of group IID, IIE, and XII sPLA 2 s in the culture media of mammalian cells transfected with the genes coding for these enzymes is barely detectable (38,41,43,49,64,65). It may be noted that porcine and bovine pancreatic group IB sPLA 2 s display true interfacial allosteric activation (k cat * and K m * type) upon binding to the vesicle interface (3), although this activation is not yet fully understood at the molecular level.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, 5 l of the DNA-free RNA preparations from Ficoll-enriched or FACS-sorted CD16 ϩ human neutrophils or 2 g of DNA-free RNA extracted from myocardial tissue (Ambion, Austin, TX) was reverse-transcribed using 40 units of Moloney murine leukemia virus-reverse transcriptase in the presence of 0.5 g of oligo(dT 18 ) primers, 50 mmol/liter Tris-HCl, pH 8.3, 50 mmol/liter KCl, 4 mmol/liter MgCl 2 , 10 mmol/liter dithiothreitol, deoxynucleotide (dNTP) mix (1 mmol/liter each), and 20 units of RNase inhibitor. The reaction mixture was incubated for 60 min at 39°C (transcription) and 10 min at 70°C (inactivation of RT).…”
Section: Rna Extraction and Reverse Transcription-ficoll-enriched Ormentioning
confidence: 99%
“…GIIC sPLA 2 is present in the mouse but appears as a pseudo gene in humans (4). GIID sPLA 2 mRNA was detected in human spleen, thymus, small intestine, colon, lung, pancreas, and placenta (17,18), whereas GIIE sPLA 2 expression in humans is restricted to the brain, heart, lung, and placenta (19). mRNA coding for GIIF sPLA 2 has been identified in many human tissues, with the highest levels detected in the placenta, thymus, prostate, testes, kidney, liver, and thyroid (17).…”
mentioning
confidence: 99%
“…In the last few years, six mouse and five human sPLA 2 s structurally related to GIB and GIIA sPLA 2 s (mGIIC, hGIID, mGIID, hGIIE, mGIIE, mGIIF, hGIIF, hGV, mGV, hGX, and mGX) 2 have been identified (15)(16)(17)(18)(19)(20). 3 All of these group I/II/V/X sPLA 2 s have similar primary structures, including identical catalytic site residues and partially overlapping sets of disulfides (21).…”
mentioning
confidence: 99%